Analisis Kepastian Hukum Sertipikat Ganda dalam Sistem Pertanahan Terintegrasi di Era Digital - Nurul Khusna Ramadhani; Sanusi Sanusi; Tiyas Vika Widyastuti (Journal of Contemporary Law Studies, 2026)
This study aims to analyze the extent to which legal certainty of land ownership can be ensured in cases of dual land certificates within Indonesia’s integrated digital land administration system. The research adopts a normative-empirical approach, combining a legislative review with case study analysis. Data were collected through document analysis of relevant regulations, including Law No. 5 of 1960 concerning Basic Agrarian Principles, and the Supreme Court Decision No. 309 PK/Pdt/2021, and were analyzed descriptively using qualitative methods. The findings reveal that legal certainty in land ownership remains inadequately guaranteed, as evidenced by the persistent occurrence of dual certificates over the same land object. This problem is primarily caused by weaknesses in land administration, inconsistencies between physical and juridical data, and administrative negligence in certificate issuance. Although the digitalization of land administration through an integrated system and electronic certificates aims to strengthen preventive mechanisms by establishing a unified national database, its effectiveness is still limited. In conclusion, the integrated digital land system functions as an administrative tool to reduce disputes and improve data accuracy; however, it does not provide absolute legal certainty. The realization of stronger legal certainty depends on improving data quality, institutional capacity, technological infrastructure, and public digital literacy.